Influence of calcium propionate on starter pig performance - Real, D.E.; Woodworth, J.C.; Webster, M.J.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 24-d growth study was conducted to evaluate the effects of low rates of a dietary acidifier, calcium propionate, on weanling pig growth performance. Experimental diets, fed from d 0 to 10, were a control diet with no acidifier, the control diet with 4 lb/ton of Kemgest, or the control diet with 4 or 8 lb/ton calcium propionate. From d 10 to 24, pigs were fed a common phase II diet containing no acidifier. Adding a low rate of acidifier to the diet had no influence on pig performance.
Keywords: Swine; Acidifiers; Nursery pigs; Calcium propionate